2023
DOI: 10.3390/app13031308
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity of Shallow Foundations on Unsaturated Silty Soils

Abstract: In general, the ultimate bearing capacity (UBC) of shallow foundations on unsaturated soils is characterized by the conventional shear strength (SS) parameters in which saturated theories are applied. However, in this case, it is clear that the foundations designed using the obtained values from the saturated cases not be economical. In recent years, procedures have been developed to estimate the UBC of foundations on unsaturated soils, that take into account drained and undrained loading conditions. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In addition, the cohesion and the angle of internal friction decreased as the moisture content increased. (Yilmazoglu and Ozocak, 2023) derived a formula to calculate the ultimate bearing capacity of shallow foundations (new unsaturated silt-sand soils) through direct shear tests on different unsaturated silty soils. (Uyeturk and Huvaj, 2021) performed direct shear tests on compacted residual soils and found that soil shear strength increased as soil saturation decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cohesion and the angle of internal friction decreased as the moisture content increased. (Yilmazoglu and Ozocak, 2023) derived a formula to calculate the ultimate bearing capacity of shallow foundations (new unsaturated silt-sand soils) through direct shear tests on different unsaturated silty soils. (Uyeturk and Huvaj, 2021) performed direct shear tests on compacted residual soils and found that soil shear strength increased as soil saturation decreased.…”
Section: Introductionmentioning
confidence: 99%